Memo to Shanghai - Hunn, Deborah (John Curtin Gallery, 2022)
The short experimental auto-fiction work "Memo to Shanghai" engages in a creative and generative dialogue with Isaac Julien's art work 'Ten Thousand Waves'. Julien's piece is an immersive film installation first exhibited in Europe in 2010, and displayed at the John Curtin Gallery as part of an exhibition of Julien's work in 2022. 'Memo to Shanghai' responds to 'Ten Thousand Waves' representation of Shanghai through memories of travel in Shanghai and the subsequently formulated retrospective lens of the Covid 19 pandemic, exploring how the latter can produce a radically altered sense of place, self, memory. and the cross cultural encounter. 'Memo to Shanghai' was written and performed by the author as a part of the 2022 event, 'A Thousand Words: Curtin Writers’ Response to Isaac Julien' held and recorded at the John Curtin Gallery, Curtin University, Wester Australia in March 2022 and then released for public online viewing. The work is viewable at the 26 min mark of the video recording.